An evaluation method for product design solutions for healthy aging companionship - Hu, Shan; Jia, Qi; Dong, Linlin; Han, Jialin; Guo, Min; Guo, Weiqi (Frontiers in Public Health, 2022)
Background: With the development trend of healthy aging and intelligent integration, escort products have become a new means of healthy aging. Healthy old-age care pays attention to the convenience and informatization of life. In order to meet the needs, designers often design multiple accompanying product solutions., and it is very important to use reasonable evaluation methods to decide the optimal solution. Purposes: A new comprehensive evaluation method is proposed to reduce the subjectivity and one-sidedness of the selection process of intelligent escort product design solutions, make the decision more objective and reasonable. Such decision can enhance the experience and naturalness of the elderly using intelligent products. Methods: Firstly, a large number of user interviews were analyzed using the grounded theory, gradually refine through theoretical coding, and abstract the design scheme evaluation index. Secondly, the idea of game-theoretic weighting is used to optimise a linear combination of subjective and objective weights to determine the final weights of each evaluation indicator. Finally, the evaluation and selection is completed based on the solution ranking determined by the approximate ideal solution ranking method (TOPSIS). It is applied to the selection of the elderly escort robot design, and the usability test is conducted using the PSSUQ to verify the selection results. Results: The new comprehensive evaluation method can better complete the preferential selection of product design solutions for healthy aging escorts, and reduce the subjectivity and one-sidedness of the evaluation. Conclusions: This method compensates for the reliance on personal experience in the selection of options, improve the subjectivity of the evaluation index determination process and the deviation of index weighting. Improve the objectivity and scientificity of decision-making, thereby reducing the blindness of design and production. It also provides theoretical reference for the research scholars of healthy aging companion products.